VDRL titres in early syphilis before and after treatment. Issue 2 (April 1992) - Talwar, S; Tutakne, M A; Tiwari, V D
Abstract : OBJECTIVE--To observe the pretreatment VDRL titres in different stages of early syphilis and evaluate the changes in VDRL titre following treatment using different treatment schedules. DESIGN--Retrospective study was carried out by analysing the records of cases of early syphilis treated between 1976 to 1981. SETTING--Armed Forces personnel treated at different service hospitals in India. SUBJECTS--Of 3183 cases of early syphilis treated with different regimens during this period, 1532 were fully followed-up for a period of 30 months. Records of these 1532 cases were analysed. MAIN OUTCOME MEASURES--Assessment of VDRL titres before treatment and during post treatment surveillance period of 30 months. Attainment of non-reactivity of VDRL test in various stages of early syphilis using different treatment schedules was evaluated. RESULTS--Relatively higher titres were observed in secondary syphilis. Following treatment it was observed that VDRL test was still reactive at the end of 6 months in 16.47% of primary, 27.56% of secondary and 18.95% of early latent cases; at the end of 12 months in 11.38% of primary, 17.25% of secondary and 15.79% of early latent cases while at 30 months reactivity was still observed in 6.60% of primary, 8.39% of secondary and 11.58% of early latent cases. CSF was examined in 1173 cases at 6 months, of which one case revealed VDRL reactivity while two cases showed reactivity amongst 1188 CSF examined at 30 months. There has been no significant difference with broad spectrum antibiotics and 2.4 MU benzathine penicillin. Results were better with 4.8 MU benzathine penicillin and procaine penicillin. CONCLUSION--VDRL test appears to be a reliable test for the follow-up of treated patients in early syphilis. Early treatment prevents development of seropositivity in seronegative syphilis while majority of seropositive cases attain seronegativity by 6 months. Higher doses of benzathine penicillin and procaine penicillin accelerate the speed of seroconversion.